Coordinated Energy Management Scheme for Ship-Harbour Energy System Based on Economic Optimal Scheduling - Zhang, Yuxin; Shan, Qihe; Teng, Fei; Li, Tieshan (2021 International Conference on Security, Pattern Analysis, and Cybernetics（SPAC, 2021)
With the development of renewable energy technology, and combined with the traditional fuel energy as an energy system, which integrated with load equipment to form a ship-harbour energy system. In order to ensure the safe operation of the energy system, we take a limitation on the carbon dioxide emissions of the ship during sailing voyage to reduce the waste of resources caused by redundant energy generation. Therefore, based on the above situations, an energy management model is proposed in this paper. In addition, considering the above problem, a reliable and efficient distributed economic optimal scheduling strategy is constructed. The simulation results show that the method can provide high-precision multi-energy complementary optimal scheduling scheme for the ship-harbour energy system under the premise of convergence.